Analysing relationship between productivity and knowledge economy data of EU countries (including Turkey) by using canonical correlation analysis. (1st January 2012) - Burmaoglu, Serhat; Kazancoglu, Yigit; Kabak, Mehmet
For the last 200 years, neo-classical economies have recognised only two factors of production: labour and capital. Knowledge, productivity, education and intellectual capital were all regarded as exogenous factors that are falling outside the system. Knowledge is a part of production systems in emerging economies. Also relationship between knowledge and productivity is an important aspect either. This study aims to find a relationship between the knowledge economy and the productivity for EU countries (including Turkey) using canonical correlation analysis. In contrast to previous works, instead of using firms' data, the macroeconomic data of countries is used for the analysis. The aim of this study is to find which of the knowledge economy variables has the most significant correlation between productivity variables, and also the possibility of existence of gender-based relations is scrutinised. According to the results of the analysis, patent number, computer usage and internet access level have significantly affected productivity. On the other hand, gross domestic product per capita as a productivity variable also has significant effect on knowledge economy variables. For gender-based variables, however, no correlation has been extracted. Finally, the results are discussed in the final section and some comments about knowledge economy and productivity are made.